2015
DOI: 10.1016/j.joca.2015.05.026
|View full text |Cite
|
Sign up to set email alerts
|

Compositional MRI techniques for evaluation of cartilage degeneration in osteoarthritis

Abstract: Osteoarthritis (OA), a leading cause of disability, affects 27 million people in the United States and its prevalence is rising along with the rise in obesity. So far, biomechanical or behavioral interventions as well as attempts to develop disease-modifying OA drugs have been unsuccessful. This may be partly due to antiquated imaging outcome measures such as radiography, which are still endorsed by regulatory agencies such as the United States Food and Drug Administration (FDA) for use in clinical trials. Mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
196
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(205 citation statements)
references
References 132 publications
0
196
0
3
Order By: Relevance
“…Compositional MRI techniques such as delayed gadolinium-enhanced MRI of cartilage (dGEMRIC), T2, T1rho, T2*, gagCEST, and sodium imaging all attempt to measure the biochemical composition of cartilage [12]. T2, T1rho, and dGEMRIC have been studied extensively in the knee, whereas most studies in the hip, to date, used dGEMRIC.…”
Section: Introductionmentioning
confidence: 99%
“…Compositional MRI techniques such as delayed gadolinium-enhanced MRI of cartilage (dGEMRIC), T2, T1rho, T2*, gagCEST, and sodium imaging all attempt to measure the biochemical composition of cartilage [12]. T2, T1rho, and dGEMRIC have been studied extensively in the knee, whereas most studies in the hip, to date, used dGEMRIC.…”
Section: Introductionmentioning
confidence: 99%
“…T1 rho probes slow motion interactions between motion-restricted water molecules and their local macromolecular environment. In vitro studies demonstrated that depletion of proteoglycan resulted in increased T1 rho values, suggesting T1 rho estimates proteoglycan content 86,87 . There is some evidence that other factors, including collagen fiber orientation and concentration of other macromolecules, may contribute to T1 rho values 88 .…”
Section: Quantitative Mr Imaging Biomarkersmentioning
confidence: 98%
“…Resolution requirements to detect fissuring and fraying of cartilage are quoted at ∼0.3 mm, in‐plane . In contrast, compositional assessment of cartilage aims to evaluate molecular status of the fluid‐filled collagen and proteoglycan network comprising hyaline articular cartilage . Compositional cartilage imaging includes techniques such as T 2 mapping, delayed gadolinium enhanced magnetic resonance imaging of cartilage (dGEMRIC), sodium ion imaging, T 1 ρ ( T 1 rho) mapping, and diffusion‐weighted imaging …”
Section: Advanced Cartilage Imagingmentioning
confidence: 99%
“…3D FSE techniques have demonstrated diagnostic accuracy similar to that of 2D FSE techniques . The 3D SPGR sequence, sometimes referred to as FLASH, is available for clinical use on many MRI systems . The main limitation of SPGR is the decreased contrast (compared to T 2 or proton density) between joint fluid and articular cartilage, which somewhat limits its sensitivity for surface defects .…”
Section: Advanced Cartilage Imagingmentioning
confidence: 99%